AMORPHOUS AND NANOCRYSTALLINE MATERIALS FOR APPLICATIONS AS HARD AND SOFT MAGNETS - Reiko Sato; Roland Grﬁssinger (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2003)
In the last years great effort was made to improve the magnetic properties of hard and soft magnetic materials. Permanent magnets based on Nd-Fe-B with an energy product of45 1k J/m3 were recently reported Any significant further improvement needs a new compound with a higher saturation magnetization.